Morphological and molecular characterization of Travassosinema claudiae n. sp. (Oxyuridomorpha: Travassosinematidae) from the Japanese millipede Parafontaria laminata (Attems, 1909) (Polydesmida: Xystodesmidae) - Morffe, Jans; Hasegawa, Koichi (Zootaxa, 2017)
Travassosinema claudiae n. sp. is described from the hindgut of the polydesmid millipede Parafontaria laminata (Attems, 1909) (Polydesmida: Xystodesmidae) from Aichi prefecture, Japan. Females of the new species resemble T. thyropygi Hunt, 1996 and T. travassosi Rao, 1958 by lacking lateral alae and the constriction of the body posterior to the level of the vulva. T. claudiae n. sp. differs from T. thyropygi by its shorter body and tail, and larger eggs. Also, the nerve ring is located in the procorpus-isthmus junction in opposition to T. thyropygi, where the nerve ring is just anterior to the basal bulb. T. claudiae n. sp. can be differentiated from T. travassosi by its shorter eggs and less extended cephalic umbraculum. Males of T. claudiae n. sp. are more similar to those of T. dalei Spiridonov & Cribb, 2012 by having a similar body length, form of the oesophagus, structures around the cloaca (mid-ventral, digitiform pre-cloacal pair of papillae, a large pair of adcloacal papillae and the anterior lip of cloaca ornamented and with a spatula-like post-cloacal projection), absence of spicule and gubernaculum, and presence of a tail filament. T. claudiae n. sp. differs by the position and type of ornamentation of the large ornamented pair of papillae, by lacking the minute pair of papillae in the tail filament and by the presence of lateral alae. Description is supplemented by SEM images. The phylogeny of the species is inferred by D2-D3 28S LSU rDNA and 18S SSU rDNA. This constitutes the first species of the genus Travassosinema Rao, 1958 described from Japan.